0.2 to 10 keV electrons interacting with water ice: Radiolysis, sputtering, and sublimation. (June 2018) - Galli, A.; Vorburger, A.; Wurz, P.; Pommerol, A.; Cerubini, R.; Jost, B.; Poch, O.; Tulej, M.; Thomas, N.
Abstract: We present new laboratory experiments investigating various water ice samples, ranging from thin ice films to porous thick ice layers, that are irradiated with electrons. The molecules leaving the ice are monitored with a pressure gauge and a mass spectrometer. Most particles released from the ice are H2 and O2, the observed ratio of 2:1 is consistent with H2 O being radiolysed into H2 + 1/2 O2 upon irradiation. H2 O2 is likely a minor contribution of radiolysis, amounting to 0.001 ± 0.001 of the total gas release from the ice sample. Neither the physical properties of the ice, nor the energy, nor the electron impact angle have any obvious effect on the relative abundances of the radiolysis products. The absolute sputtering yield (i.e., the ratio of produced O2 or destroyed H2 O per impacting electron) increases with energy until a few 100 eV. For higher energies up to 10 keV the yield remains roughly constant, once the saturation dose of the ice is reached. This indicates that ongoing irradiation eventually releases the radiolysis products from the water ice even for penetration depths of several micrometers. Highlights: First experimental sputtering yields for energetic electrons between 0.2 and 10 keV irradiating water ice. Yields tested for a wide range of physical properties (compact ice films, frost and thick porous ice samples). Most H2 O molecules are lost from the surface via radiolysis as H2 + 1/2 O2 . The relative abundance of H2 O2 was 0.001 ± 0.001. Electron irradiation seems to be relevant for the creation of oxygen-rich atmospheres of icy moons like Europa and Ganymede.